2017
DOI: 10.1099/jmm.0.000645
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Pichia kudriavzevii fungaemia in a neonatal intensive care unit

Abstract: This study emphasizes the importance of accurate identification of the aetiological agent of sepsis and vigilant monitoring for the possibility of an outbreak in NICUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…13) Although C. albicans is the most prevalent species involved in mucocutaneous and disseminated infections, the incidence of candidiasis due to non-albicans Candida spp. is increasing, [57][58][59][60][61][62][63] among which C. glabrata, C. tropicalis, C. parapsilosis, and C. krusei are the major isolates. These species are inherently resistant or acquire resistance, or both, to commonly used antifungal drugs, such as fluconazole, and, thus, the identification of species of Candida is important for selecting therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13) Although C. albicans is the most prevalent species involved in mucocutaneous and disseminated infections, the incidence of candidiasis due to non-albicans Candida spp. is increasing, [57][58][59][60][61][62][63] among which C. glabrata, C. tropicalis, C. parapsilosis, and C. krusei are the major isolates. These species are inherently resistant or acquire resistance, or both, to commonly used antifungal drugs, such as fluconazole, and, thus, the identification of species of Candida is important for selecting therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…anamorph) of the corresponding sexual form (teleomorph) of P. kudriavzevii. Strains of P.kudriavzevii are recognized as fermenting, not pathogenic, fungi, are widely distributed in nature, and are often encountered in spontaneous fermentations and used to produce traditional fermented foods [61][62][63][64]. Recent studies strongly suggested that clinical andBiological and Pharmaceutical Bulletin Advance Publicationenvironmental strains are similar.…”
mentioning
confidence: 99%
“…Here, we utilized the most robust and reproducible typing method, FAFLP technique to establish genetic relatedness among blood and environmental isolates. Previously, we reported the effectiveness of AFLP in determining genetic relatedness of isolates due to other fungi from our centre [8,9,29,[34][35][36]. Clustering of environmental isolates with the majority of the blood isolates indicates the hospital environment as the major source of infection.…”
Section: Discussionmentioning
confidence: 94%
“…Non-albicans Candida or other species including Pichia kudriavzevii, Kodamaea ohmeri Candida tropicalis or Cryptococcus albidus have been more frequently isolated from hospitalized patients [1,2,3,4,7,9]. These species seem to be very virulent and often show resistance to the commonly used antifungal treatments [5,7,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…In order to find yeast species which are able to inhibit cell division of the disease-associated species, such as Pichia kudriavzevii, Kodamaea ohmeri, Candida tropicalis, Cryptococcus albidus [1,2,3,4,5,6,7,8], several yeasts were investigated. The test yeast strains were divided into two groups.…”
Section: Metschnikowia Andauensis Pichia Anomala Candida Tropicalismentioning
confidence: 99%